Evolution of cavities of not spherical form in a liquid - Буйвол, В.М. (Proceedings of National Aviation University (archive), 2005)
Evolution of cavities of not spherical form in a liquid is considered. The mathematical model of dynamics of a cavity in a liquid offered. Forms ellipsoidal cavities and their dependence on the moments of time are determined take info account of influence of a field of a gravity.